TRANSFORMASI NILAI-NILAI BUDAYA ARAB DALAM TRADISI PERKAWINAN ADAT PALEMBANG - Apriana, Apriana; Fatmah, Fatmah; Yulisa, Wetika (Raudhah - Proud To Be Professional, 2025)
Transformation is a change from old to new due to adaptation to the environment. In the marriage customs of the Palembang community, if observed, there are many transformations of Arab cultural values, which are interesting to do research. The results of the study show that the transformation of Arab cultural values ​​in the Palembang traditional marriage tradition is motivated by several things, first: the history and spread of Islam in Palembang. Second, the transformation occurs closely with Islamic teachings. Third, the transformation occurs greatly influenced by Islamic religious values. Furthermore, the transformation of Arab culture in the Palembang traditional marriage tradition can be seen when getting married, wearing wedding clothes and using traditional music to accompany the bride and groom. The impact of the transformation of Arab cultural values ​​in the Palembang traditional marriage tradition is social change with the integration of Islamic values ​​from Arab culture, the strengthening of identity for some people, the development of this transformation culture can also be seen as part of the dynamics of cultural development that continues to change.